Systems and Synthetic Biology of Forest Trees: A Bioengineering Paradigm for Woody Biomass Feedstocks - Myburg, Alexander A.; Hussey, Steven G.; Wang, Jack P.; Street, Nathaniel R.; Mizrachi, Eshchar (Frontiers in Plant Science, 2019)
Fast-growing forest plantations are sustainable feedstocks of plant biomass that can serve as alternatives to fossil carbon resources for materials, chemicals and energy. Their ability to efficiently harvest light energy and carbon from the atmosphere and sequester this into metabolic precursors for lignocellulosic biopolymers and a wide range of plant specialized metabolites make them excellent biochemical production platforms and living biorefineries. Their large sizes have facilitated multi-omics analyses and systems modelling of key biological processes such as lignin biosynthesis. High-throughput ‘omics approaches have also been applied in segregating tree populations where genetic variation creates abundant genetic perturbations of system components. This has allowed construction of the first systems genetics models linking genes and pathways to complex trait variation. With this information in hand, we can now contemplate the use of synthetic biology and genome editing techniques in a bioengineering approach based on a deeper understanding and rational design of biological parts, devices and integrated systems. However, the complexity of the biology and interacting components will require investment in big-data informatics, machine learning and data visualization to fully explore multi-dimensional patterns and identify emergent properties of biological systems in trees. Besides reviewing recent progress in the application of systems and synthetic biology in trees, we propose a bioengineering paradigm that, together with accelerated genomic breeding, could facilitate the development of a new generation of woody biorefinery crops.